Analisis faktor-faktor yang mempengaruhi pendapatan rumah tangga miskin di Kabupaten Tanjung Jabung Barat (studi kasus di Desa Semau Kecamatan Bram Itam) - Ahmad Rafii; Yulmardi Yulmardi; Adi Bhakti (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
The research aims to 1). Knowing the socioeconomic characteristics of poor households 2). Knowing the effect of working hours, education, age, and land area on the income of poor households in Semau Village, Bram Itam District, Tanjung Jabung Barat Regency. The research used descriptive analysis method and quantitative analysis with multiple linear regression analysis. Based on the results of the analysis of the characteristics of poor households in Semau villages, dominated by the age of 15-64 years (61.01%), the work of farmers (53.22%), the average income is IDR 650,000 (41-9%), work 180-230 hours (61.29%), education level did not complete elementary school (43.5%), age> 50 years (53.2%), land area (64.5%). Simultaneously the outpouring of working hours, education, age, and land area have a significant effect, partially education and land area have a positive and significant effect, the number of working hours and age do not have a significant effect on the income of poor households in Semau Village, Bram Itam District, Tanjung Jabung Barat Regency. Keywords: Socio-economic characteristics, Income, Work hours expenditure, education, Age, Land area